Prevalence of Dry Eyes Sindroma Post Operating Cataract with Facoemulsification Techniques at Family Medical Center Hospital - Michael Indra Lesmana; Ritsia Anindita Wastitiamurti; Sri Harto; Carrent Liliyanti Dwibulan (Jurnal MedScientiae, 2023)
Dry eye syndrome is a condition characterized by dryness of the surface of cornea and conjunctiva caused by reduced tear function. One the factors that cause this is cataract surgery. This study aims to look at the magnitude of the prevalence of dry eye syndrome after cataract surgery with phacoemulsification techniques at the Family Medical Center hospital in the July 2019 period. This study uses a quantitative descriptive method with a cross-sectional approach. Data collection was performed using primary data with a total sampling technique. Total samples obtained were 70 eyes with a total of 43 respondents. This data was processed using SPSS 16.0 for Windows. The results of this study showed that the majority of sufferers of dry eye syndrome after cataract surgery were mostly female (68.2%) and in the age group ≥ 50 years (72.7%), (48.8%) complained of a lump and (37, 2%) complained of watery eyes. The severity of the degree of dry eye that occurs in mild respondents (68.2), and moderate degrees (31.8).